Implementation of the Legal Justice Concept in Indonesia: Study of John Locke's Perspective - Abdul Haris Alifianto; Belva Vidaloka Chrisari; Dominikus Rato; Fendi Setyawan (Rechtenstudent, 2024)
Law serves as the fundamental cornerstone of society, crucial for maintaining order and addressing societal challenges. Within a rule of law framework, the availability of legal sources facilitates the exploration and understanding of legal principles. However, the concept of justice, inherent to human existence, remains elusive and multifaceted, defying simple translation. This study aims to delve into the essence of justice from a legal philosophical perspective. Employing a normative juridical approach, data collection includes diverse scholarly materials and legal documents. The findings underscore the significance of justice as a pivotal concept in human affairs, transcending disciplinary boundaries. Moreover, within legal philosophy, justice emerges as a guiding principle embedded in the fabric of law, grounded in righteousness, fairness, and accountability.